THE USE OF P.O.W.E.R. LEARNING AS A LEARNING STRATEGY TO IMPROVE STUDENTS WRITING COMPETENCY - Rissa San Rizqiya; Mundriyah Yudhi Pamungkas; Ratih Inayah (OKARA: Jurnal Bahasa dan Sastra, 2017)
This research is one of the recipients of Research Grants for Beginner Lecturers (Hibah Penelitian Dosen Pemula) organized by Kemenristek Dikti with the year of implementation of 2017. This study aims to: (1) examine the influence of P.O.W.E.R. learning on the effectiveness of students’ learning; and (2) analyze students' writing skills after applying the P.O.W.E.R strategy learning. It is a qualitative descriptive research where the primary data analyzed is the development of student writing before, during, and after the implementation of P.O.W.E.R. Learning. In addition, as secondary data, the analysis of questionnaires, interviews, and classroom observations were tabulated as supporting primary data. Participants selected by using Purposive Participant technique. A total of 80 regular students of the 2016 English Study Program at STKIP Siliwangi were involved. The results of the study showed an increase in students writing skill form before the implementation, during, and after the implementation of P.O.W.E.R. Learning. Based on questionnaire and observation, student also responses positively to the lessons learned. This implies that the students were motivated by the learning process. Thus it can be concluded that P.O.W.E.R. Learning affects the effectiveness of students learning through the realization of learning styles as well as increased learning motivation.